Exploring new forms of cooperation between China and Latin America and the Caribbean (UN ECLAC SantiagoCL, 2018)
Covers key issues in the relationship between Latin America and the Caribbean and China. Analyses the current internation economic situation; the social context in the region and in China and the common challenges facing both in the areas of eradicating poverty and making progress with education and health. Provides an overview of bilateral trade and notes that the diversification of the region's export basket to China is still the main challenge it faces. Highlights the opportunities that exist for building a renewed relationship in the areas of foreign direct investment (FDI). Examines the shared challenge of climate change and the mitigation commitments that both sides have assumed. Provides a comparison of the region and China in terms of their policies for research and development, human resource training. Gives some proposals for furthering different forms of cooperation between Latin America and the Caribbean and China.
Keywords: FOREIGN RELATIONS